Best-seller, a relevância de um gênero como desafio do gosto literário: Um estudo sobre a obra de Paulo Coelho - Menezes, Arlania Maria Reis de Pinho (2011)
This work intends to analyze the elements that underpin the success of best sellers, both in sales and in reception, highlighting their basic characteristics, as well as their relevance to the taste of the consumer-reader. Best-Seller is a book that has sold thousandsof copies, translations into several languages, is sales success(thus, the product market), whose structural characteristics and themes of the narrative is quite close to trivial. However, to be out of institutionalized patterns, this genre is seen as a subculture and itsreader, consequently, is also disqualified. Using the theoretical studies on the concept of Best-Seller, narrative trivial, publishing,receiving and taste (or preference) of the reader, a mapping was performed on this type of narrative, for this, we analyzed some novels of the writer Paulo Coelho, an object of study as a writer ofbest-sellers, taking into account that, despite the great success inproduction, sales and reception, passes the scrutiny of literary criticism as a non-writer. This reflection on the differences andemerged in contemporary literary novelties, which circulatepositively receptive, it is necessary to situate them within a social and literary. And the Best-Seller is in that position of conflict, as a genre is not institutionalized, so it follows the "rules" that determinea narrative as literature.